Exogenous Nitric Oxide and Phosphorus Stress Affect the Mycorrhization, Plant Growth, and Associated Microbes of Carya illinoinensis Seedlings Colonized by Tuber indicum - Zhang, Xiaoping; Li, Xiaolin; Wu, Chenguang; Ye, Lei; Kang, Zongjing; Zhang, Xiaoping (Frontiers in Microbiology, 2019)
Ectomycorrhizal colonization level, host plant quality and the associated microbes in rhizosphere soil are of vital importance to the artificial cultivation of truffles. To explore the effects of nitric oxide (NO) and phosphorus (P) stress on the symbiosis of truffles and host plants, different concentrations of exogenous NO donor sodium nitroprusside (SNP) and P were applied to Carya illinoinensis seedlings inoculated with Chinese black truffle (Tuber indicum). The colonization rate of T. indicum and the growth of the seedlings were then investigated. Additionally, the norB-type denitrifying bacterial community and fungal community in the rhizosphere soil of the host were analyzed by high-throughput sequencing. The results showed that the colonization rate of T. indicum was significantly influenced by SNP treatments and P stress, with the highest level being obtained when the SNP was 100 μmol/L under low P stress (5 μmol/L). Treatment with 100 μmol/L SNP alone also increased the colonization rate of T. indicum and had positive effects on the plant height, stem circumference, biomass, root-shoot ratio and root POD activity of the seedlings at different times after inoculation. Under low P stress, the 100 μmol/L SNP increased the richness of the norB-type denitrifying bacterial community. Interestingly, the diversity and richness of norB-type denitrifying bacteria were significantly correlated with the colonization rate of T. indicum. SNP treatments altered the abundance of some dominant taxa under low P stress such as Alphaproteobacteria, Gammaproteobacteria, Pseudomonas, Ensifer, and Sulfitobacter. Evaluation of the fungal community in rhizosphere soil revealed that 100 μmol/L SNP treatment alone had no obvious effect on richness and diversity, but it did shape the abundance of some fungi. Buellia, Podospora, Phaeoisaria, Ascotaiwania and Lophiostoma were more abundant following exogenous NO application, while the abundance of Acremonium, Monographella and Penicillium were decreased. Network analysis indicated T. indicum was positively or negatively correlated with some fungal genera when treated with 100 μmol/L SNP. Overall, these results revealed how exogenous NO and P stress influenced the symbiosis of truffles and host plants and indicate that application of SNP treatments has the potential for ectomycorrhizal synthesis and truffle cultivation.